Investigating the role of ASCC1 in the causation of bone fragility - Voraberger, Barbara; Mayr, Johannes A.; Fratzl-Zelman, Nadja; Blouin, Stéphane; Uday, Suma; Kopajtich, Robert; Koedam, Marijke; Hödlmayr, Helena; Wortmann, Saskia B.; Csillag, Bernhard; Prokisch, Holger; van der Eerden, Bram C. J.; et al. (Frontiers in Endocrinology, 2023)
Bi-allelic variants in ASCC1 cause the ultrarare bone fragility disorder ‘spinal muscular atrophy with congenital bone fractures-2’ (SMABF2). However, the mechanism by which ASCC1 dysfunction leads to this musculoskeletal condition and the nature of the associated bone defect are poorly understood. By exome sequencing, we identified a novel homozygous deletion in ASCC1 in a female infant. She was born with severe muscular hypotonia, inability to breathe and swallow, virtual absence of spontaneous movements, and showed progressive brain atrophy, gracile long bones, very slender ribs, and a femur fracture and died from respiratory failure aged 3 months. A transiliac bone sample taken post-mortem revealed a distinct microstructural bone phenotype with low trabecular bone volume, low bone remodeling, disordered collagen organization, and an abnormally high bone marrow adiposity. Proteomics, RNA sequencing, and qPCR in patient-derived skin fibroblasts confirmed that ASCC1 was hardly expressed on protein and RNA level compared to healthy controls. Furthermore, we demonstrate that mutated ASCC1 is associated with a downregulation of RUNX2, the master regulator of osteoblastogenesis, and SERPINF1, which is involved in osteoblast and adipocyte differentiation. It also exerts an inhibitory effect on TGF-β/SMAD signaling which is important for bone development. Additionally, knockdown of ASCC1 in human mesenchymal stromal cells (hMSCs) suppressed their differentiation capacity into osteoblasts while increasing their differentiation into adipocytes. This resulted in reduced mineralization and elevated formation of lipid droplets. These findings shed light onto the pathophysiologic mechanisms underlying SMABF2 and assign a new biological role to ASCC1 acting as an important pro-osteoblastogenic and anti-adipogenic regulator.